DIFFERENT SEQUENTIAL CROPS AFTER MAIZE ON WEED POPULATION DYNAMICS - SODRÉ FILHO, Joilson; CARMONA, Ricardo; CARDOSO, Alexandre Nunes; CARVALHO, Arminda Moreira de (Scientia Agraria, 2008)
The objective of this study was to test the efficiency on weed control of the crops sowed after maize (black oat, sunnhep, canavalia, pigeonpea, mucuna, sunflower and millet) in conventional tillage and no-tillage in Cerrado. Weed dry phytomass was measured after 60 days of the sequential crops sowing date. Weed density was evaluated after 30 and 60 days of the sequential crops sowing date, and after 45 days of maize sowing date. Weed seed bank in the soil was estimated in July of 2001 and 2002. Black oat, canavalia, sunflower, pigeonpea and mucuna, sowed after maize, reduced weed dry phytomass. No-till reduced soil seed bank, but increased weed emergency in the field, compared to the conventional system. The use of sequential crops with no-till management decreases the weed seed bank in soil.